Penerapan E-Government terhadap Pengurusan Legalitas Usaha di Kelurahan Wonorejo, Kecamatan Tegalsari, Kota Surabaya - Azizah, Nurul; Marshanda, Anasthasia; Fitrah, Aldisa Raihan; Amalina, Alya Nur (Jurnal Bisnis Indonesia, 2024)
Micro, Small and Medium Enterprises (MSMEs) are creative economic businesses that were born asone of human activities in fulfilling their daily needs. In order for MSMEs to compete in the freemarket era, one of the conditions is the fulfillment of business legality. Recently, the governmentissued a new policy regarding the legality of MSME businesses that can be done online , namelythrough the Online Single application and web Submissions . This policy concerns the renewal of oldpublic services into E- Government -based public services . Business legality is an important elementas an indication of identity that a business entity is legal and legally valid so that it is recognized bythe community. Management of business legality is an absolute must for every business actor.Wonorejo is one of the villages in Tegalsari District , Surabaya City where most of the people work asMSME business actors. However, there are still many MSME business actors who have not legalizedtheir business due to limited information about business legality policies, so training and assistanceare needed on managing business legality for MSME business actors in Wonorejo. The purpose of thispaper is to describe how the implementation of E- Government in business legality through a singleonline application Submission in Wonorejo through socialization, training, mentoring to the formationof business licenses in the form of NIB. This study uses a descriptive research method with aqualitative approach with a case study of business actors in Wonorejo. The results of this study areresearchers can describe how the efficiency and effectiveness, as well as several supporting andinhibiting factors that affect the application of E- Government based on a single Online application.submission (OSS) in carrying out medium to upper business license services in Wonorejo.Keywords: E- government Public Service; Business Legality